PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN CSR - Claudya, Ditta Elfratianti; Januarti, Indira (Diponegoro Journal of Accounting, 2015)
The objective of this research was to analyze which characteristics of corporate governance that influence the extent of corporate social responsibility (CSR) in companies engaged in manufacturing and mining listed in BEI and specified in sustainability reporting companies listed on IDX. Factors that were tested in this study is an independent commissioner, foreign ownership, public ownership. This sturdy uses 1 proxy that disclosure index.As the dependent variable, the research disclosure of corporate social responsibility is measured using Global Reporting Index (GRI) based on research that has been carried out by Said, et.al. in 2009. By using the method of random sampling, 97 companies of all comapnies listed on the IDX is based on the company’s sustainability report in 2013, and the data were analyzed using multiple regression. The empirical results indicate that the independent directors have a positive relationship, and significant impact on corporate social responsibility disclosure in proxy disclosure index.